Strategies for Cognitive Impairment Prevention - Ahlawat Poonam; Maheshwari Sushil Kumar; Sharma Preksha (Journal of Clinical and Biomedical Sciences)
With the ageing of the population, the prevention and treatment of cognitive impairment in the elderly have become increasingly important. This article reviews and evaluates the most recent research on therapies that may be useful in preventing cognitive impairment. Specifically, we address tactics that aim to address modifiable risk factors that may act prior to the onset of the disease. The cognitive reserve of healthy individuals can be enhanced, leading to a delay in the onset of neuropathological changes linked to dementia. Early preventative techniques include managing major depressive disorder (MDD), improving vascular risk factors including hypertension and diabetes mellitus, and changing lifestyle factors like diet, exercise, and stress reduction.